Capacitación y tecnología del proceso en la industria maquiladora - Juan Óscar Ollivier Fierro (El Colegio de la Frontera Norte, 2005)
This article attempts to show the relationship between personnel training and technological level in productive processes in the maquiladora industry, taking as a reference local manufacturing firms of a comparable size in a city in northern Mexico. The variables analyzed were the time and investment dedicated to training versus the level of technological advancement in management, production (hard technologies), and social practices (soft technologies). Statistically significant differences were found between the data for the local firms and the maquiladora firms as well as consistency in both firm types regarding training efforts and technological advancement. This highlights the strong link between human-resources strategy and technology.